Economic integration of Afghan refugees in the US, 1980-2015 - Carl Stempel; Qais Alemi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Using 1990 5% Census and American Community Survey data, we examine the economic integration of Afghan refugees to the US, focusing on employment rates and income levels. First-wave Afghan refugees (those arriving 1980-90) have made significant income and employment gains, while poverty rates and reliance on government assistance have decreased dramatically. The most recent wave is not doing as well at comparable points in time. Controlling for factors such as cultural capital, cost of living, and length of residence in the US, Afghan refugees' incomes are the lowest of seven refugee/immigrant comparison groups. This is largely explained by lower employment levels, especially among less-educated Afghan women and highly educated Afghan women and men. Factors explaining this may include Afghans' strong gender division of labour, greater levels of physical and mental disability resulting from pre-migration and migration traumas, and inability to develop occupational niches providing pipelines to jobs for recent arrivals and less-educated women. Highly educated Afghan refugees' lower income is largely explained by the low incomes of those who earned their credentials outside the US. Although unmeasured, we suspect some of the unexplained direct negative effect of Afghan refugees on income is explained by anti-Muslim and anti-Afghan prejudice.
Keywords: F22; J15; 330; Afghan; economic capital; cultural capital; integration; refugee; migration